2013
DOI: 10.1308/003588413x13625648805325
|View full text |Cite
|
Sign up to set email alerts
|

One-Stop Triple Imaging: The Way Forward in Head and Neck Cancer Management?

Abstract: Head and neck (H&N) cancer affects approximately 8–15 per 100,000 of the UK population. It has been suggested that the delay in diagnosing cancer has been a major factor in the poorer survival rates in the UK compared with some other countries in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…10 A 2013 review reported a reduction in days to diagnosis from referral date from 25.4 to 16.5 days after the introduction of same-day computed tomography and magnetic resonance imaging, which are carried out in addition to inclinic FNAC, if necessary. 11 This could be introduced at King's College Hospital if supported by financial and operational resources.…”
Section: Discussionmentioning
confidence: 99%
“…10 A 2013 review reported a reduction in days to diagnosis from referral date from 25.4 to 16.5 days after the introduction of same-day computed tomography and magnetic resonance imaging, which are carried out in addition to inclinic FNAC, if necessary. 11 This could be introduced at King's College Hospital if supported by financial and operational resources.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies evaluated the impact of a multidisciplinary clinic-based intervention whereby patients were seen by a multidisciplinary clinic to reduce the need for separate appointments. Study type varied: nine were retrospective audits, [26][27][28][29][30][31][32][33] three were before-and-after studies, [34][35][36] two were prospective audits, 37,38 and one was a retrospective cohort study. 39 One study did not have sufficient information as to the study type.…”
Section: Description Of Studies and Interventionsmentioning
confidence: 99%
“…39 One study did not have sufficient information as to the study type. 40 Seven studies were conducted in the United States, 26,27,30,35,36,39,40 five in England, 29,31,33,37,38 and one each in Australia, 28 Poland, 34 and the Netherlands. 32 Nine studies 27,30,32,[34][35][36][38][39][40] evaluated a multidisciplinary clinic, five of which 30,32,36,39,40 specified a single-day or "one-stop" multidisciplinary clinic.…”
Section: Description Of Studies and Interventionsmentioning
confidence: 99%
See 2 more Smart Citations